In Vitro Comparison of Instrumentation Time and Cleaning Capacity between Rotary and Manual Preparation Techniques in Primary Anterior Teeth - Z. Bahrololoomi; M. Tabrizizadeh; L. Salmani (Tehran University of Medical Sciences, 2007)
Objective: The aim of this study was to evaluate and compare the cleaning ability and instrumentation time of manual and rotary methods used for preparation of primary anterior teeth. Materials and Methods: Forty-four primary anterior teeth were used in this experimental study. Access cavities were prepared and India ink was injected into the canals. The samples were divided into three groups according to the instrument and preparation technique. In group I the root canals were manually instrumented with K-files. Rotary Flexmaster instruments were used for canal preparation in Group II, and the samples in Group III (control) were not instrumented. After canal preparation, the teeth were cleared with methyl salicilate and the removal of India ink was measured in the cervical, middle and apical thirds. The incidence of file breakage and instrumentation time was recorded in the three study groups. Statistical analysis was performed using Mann-Whitney and t-tests. Results: There was no significant difference in cleaning capacity between the two techniques, but a significant difference was found between the experimental and control groups. Working time was significantly shorter when using the rotary system. No file fracture was observed during the study period. Conclusion: Regarding the shorter working time for rotary instrumentation and the similar cleaning ability of the two techniques, the application of the rotary system is suggested for preparation of decidious root canals during pulpectomy.